The impact of blood pressure variability and pulse pressure on graft survival and mortality after kidney transplantation. Issue 1 (6th December 2018) - Pagonas, Nikolaos; Markakis, Konstantinos; Bauer, Frederic; Seibert, Felix S.; Seidel, Max; Zidek, Walter; Kykalos, Stylianos; Sasko, Benjamin; Klein, Thomas; Babel, Nina; Viebahn, Richard; Westhoff, Timm H.
Abstract: Background: Blood pressure variability and pulse pressure are strong and independent predictors of cardiovascular morbidity and mortality in the general population. So far, there are no data on the impact of blood pressure variability on mortality and graft survival after renal transplantation. Methods: We performed a retrospective analysis of 877 patients who underwent kidney transplantation between 1997 and 2011 in two transplant centers in Germany (Berlin and Bochum) with a follow‐up of 12‐266 months. Visit‐to‐visit blood pressure variability over the first 12 months after transplantation (3 visits) and during the first 120 months after transplantation (7 visits) was calculated as the coefficient of variation (CV = standard deviation (SD)/mean blood pressure). Patient and graft survival was defined as composite endpoint. Results: Cumulative survival was significantly higher for those patients with lower systolic blood pressure and pulse pressure within both the first 12 months and the 120 months posttransplant. After adjustment of data for gender, age, body mass index, and coronary artery disease, the cumulative incidence of the combined endpoint did not significantly differ between patients with lower vs higher CV (12 months CV hazard ratio (HR) (95% CI) = 0.90 (0.66‐1.23), P  = 0.51; 120 months CV HR (95% CI) = 0.92 (0.67‐1.26), P  = 0.60). A lower systolic blood pressure remained highly predictive for better survival in adjusted analyses. Conclusion: Visit‐to‐visit blood pressure variability is not associated with mortality or graft loss after kidney transplantation in this retrospective analysis. In analogy to the general population, however, there is an inverse relationship of survival and pulse pressure as a marker of arterial stiffness.